Impact of education policy on youth unemployment in Egypt - ISMAIL, Pensee Badr (KDI School, 2018)
Youth unemployment is a new challenge faced by a lot of countries with Egypt being no exception. This problem is more amplified in Egypt specifically due to the "youth bulge" that the labor market fails usually to absorb along with a steady rise in the number of informal jobs. The rising of this problem owes to the failure of the educational system in place whose aim is to acquire students with the needed skills necessary for a smooth transition to the labor market. The vocational education in Egypt was regarded for years as being unable to offer the above mentioned skills. In order to investigate the validity of this argument, the paper aims to look into the relationship between education and unemployment. In other words, the paper tries testing the validity of the Human capital theory in the Egyptian case. More precisely, it will provide empirical evidence on how seeking different education tracks, affects one's likelihood to be unemployed in Egypt with a special focus on youth. Also the paper will try to investigate the outcome of the 1998-2006 university entrance limitation policy on unemployment incidence. In contrast to what was argued, seeking vocational track seems to help reducing unemployment especially for young men who took the decision to seek vocational education between 2006 and 2012. It also makes individuals less prone to unemployment compared to university graduates which is totally in contrast with the Human Capital theory.
Thesis(Master) --KDI School:Master of Development Policy,2018